Manufacturing and the knowledge economy - Brinkley, Ian (London, 2009)
"This report examines the changing nature of the UK’s manufacturing sector. It argues that the traditional divide between manufacturing and services is breaking down – especially in the high-tech, knowledge intensive parts of it. Manufacturers adding service functions to their existing product portfolios is one of the key drivers of the expansion of high value service industries. The paper argues that manufacturing remains highly important to the UK’s economic performance and that it is as deserving of government support to help it through the recession as the financial service industries."